(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
This article presents the dynamics of inflation in the period from 2008 to 2019 in Russia. Inflation is monetary and non-monetary in nature, can be both hidden and open. Accurate identification of the causes of inflation will help to correctly select measures to suppress it.